Answer :

Cathenna

Answer:

[tex] \boxed{\sf (f-g)(x) = -{x}^{2} + 3x + 7} [/tex]

Given:

[tex] \sf f(x) = 3x + 1 \\ \sf g(x) = {x}^{2} - 6 [/tex]

To find:

[tex] \sf (f - g)(x) = f(x) - g(x)[/tex]

Step-by-step explanation:

[tex] \sf \implies(f - g)x = f(x) - g(x) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (3x + 1) - ( {x}^{2} - 6) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (3x + 1) + (- {x}^{2} + 6) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 3x + 1 - {x}^{2} + 6 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = - {x}^{2} + 3x + 1 + 6 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = -{x}^{2} + 3x + 7 [/tex]

Other Questions